Integrated Sustainable Agro-Maritime Village Development for Circular Economy Transformation in Kutawaru Village - Christiadi Adi Haryanto; Yusuf Effendi; Muhson Arifin; Manshur Rasyid; Duta Wahyu Wijaya (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The coastal area of Kutawaru, Cilacap, holds considerable potential in fisheries, mangrove ecosystems, agriculture, and waste management, yet remains constrained by a dominant linear economy, low commodity value-added, and weak community institutions. This study examines the implementation of the CSR program by PT Pertamina Patra Niaga Integrated Terminal (IT) Cilacap through the SEGARA KUTAWARU model (Sustainable Economy through Green Agro-Maritime Resources and Circular Approach-Kutawaru) as an effort to transform the coastal area's economy toward a circular paradigm. The program was designed based on social mapping and participatory planning with the community, resulting in four integrated sub-programs: PEPES SEGA K-CAP (coastal economic empowerment and fishing tourism), SIMANJA (mangrove conservation, educational tourism, and fishery-based SMEs), MASKUMAMBANG (integrated agriculture supported by irrigation infrastructure), and BAPAKU (community-based waste bank). Findings indicate that the integration of these four sub-programs forms a mutually reinforcing circular economic ecosystem, transforming waste into economic resources, diversifying community income, and simultaneously strengthening coastal ecosystem conservation. The SEGARA KUTAWARU model is assessed as an effective integrative framework for CSR-based coastal community empowerment and holds strong potential for replication in other coastal areas with similar characteristics.